answersLogoWhite

0

x^2 = 2x -15

x^2 - 2x + 15 = 0 where a = 1, b = -2, and c = 15

x = [-b ± √[b^2 - 4(a)(c)]]/2a

x = [2 ± √[2^2 - 4(1)(15)]]/[2(1)]

x = [2 ± √(4 - 60)]/2

x = [2 ± √(- 56)]/2

x = (2 ± i√56)/2

x = (2 ± 2i√14)/2

x = 1 ± i√14

User Avatar

Wiki User

15y ago

Still curious? Ask our experts.

Chat with our AI personalities

JordanJordan
Looking for a career mentor? I've seen my fair share of shake-ups.
Chat with Jordan
MaxineMaxine
I respect you enough to keep it real.
Chat with Maxine
SteveSteve
Knowledge is a journey, you know? We'll get there.
Chat with Steve

Add your answer:

Earn +20 pts
Q: What is the answer to x2 2x-15?
Write your answer...
Submit
Still have questions?
magnify glass
imp